دور وسائل الضبط الاجتماعي غير الرسمي في الحد من الجريمة - د. ميلاد امحمد عريشة (Aljameai, 2022)
الملخص:                         يهدف البحث للتعرف على دور وسائل الضبط الاجتماعي غير الرسمي في الحد من الجريمة، من خـــــلال الاجابة على التساؤل التالي: هل يسهم الضبط الاجتماعي غير الرسمي فعلاً في الحد من الجريمة؟، وستهدف البحث تحقيق الأتى ــ معرفة هل يسهم الضبط الاجتماعي غير الرسمي في الحد من الجريمة، وأستخدم الباحث المنهج الوصفى، وتوصل إلى عدة نتائج منها - تسهم وسائل الضبط الاجتماعي غير الرسمي في استقرار النظام الاجتماعي وأساس الحياة الاجتماعية في الحد من السلوكيات الانحرافية و الاجرامية في المجتمع - ضرورة وجود ضوابط اجتماعية بين افراد المجتمع من أجل اشباع حاجاتهم ولضمان استقرار المجتمع -  دور وسائل الضبط الاجتماعي غير الرسمي بارز وفعال في المجتمع لمالها من مركز مؤثر في حياة الافراد وفي الحفاظ على البناء الاجتماعي – و إن الثقافة المجتمعية  ذات تأثير فعال فى المجتمع فهى ترفض الجريمة وتعتبرها اجراماً خارج عن قوانينها، وهي من أهم وسائل الضبط غير الرسمي الموجودة فى المجتمع  .Abstract:      The Role of Informal Social Control in Reducing Crime. The research answered the following question - Does informal social control really contribute to reducing crime? The research aimed to achieve the following - knowing whether informal social control contributes to reducing Crime. The researcher used the descriptive approach, and reached several results, including - informal social control methods contribute to the stability of the social system and the basis of social life in limiting deviant and criminal behaviors in society The necessity of having social controls among members of society in order to satisfy their needs and to ensure the stability of society.The role of the means of informal social control is prominent and effective in society because of its influential position in the lives of individuals. Societal culture has an effective influence in society, as it rejects crime and considers it a crime outside its laws, and it is one of the most important means of informal control in society. maintaining the social structure.